Overview of Anxiety Levels of Hemodialysis Patients at Santa Elisabeth Hospital Medan 2022 - Indra Hizkia P; Sry Rumondang Sitindaon; Ervina Saro Butar-butar (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2022)
Hemodialysis is a therapy that functions as a kidney replacement. Therefore, good knowledge about hemodialysis is needed to prevent fatal events for health. As a result of this hemodialysis which can cause patients undergoing therapy susceptible to experiencing anxiety. Anxiety is a response to worry that a person gives and feels when he feels threatened and is a very normal thing in life. The literature on the incidence of depression and anxiety in the population is much larger than that found in patients with kidney disease. Data on the prevalence of depression in Indonesia is 6.1‰ and the prevalence of mental emotional disorders (anxiety) is 9.8%. The purpose of the study was to determine the level of anxiety of hemodialysis patients at Santa Elisabeth Hospital Medan in 2022. The study used a descriptive method with sampling using purposive sampling technique, totaling 36 respondents. Data analysis used univariate analysis and the results showed that the anxiety level of hemodialysis patients had a "moderate anxiety" level of 16 respondents (44.4%), who had a "severe anxiety" level of 9 (25.0%), who had a "very severe anxiety" level. ” 1 person (2.8%), who had "mild anxiety" were 8 (22.2%) and 2 person (5,6%). It was concluded that most of the respondents who underwent hemodialysis experienced moderate levels of anxiety. It is hoped that the hospital will provide spiritual assistance to provide peace so that it can reduce patient anxiety while undergoing hemodialysis.